Lean body mass is the strongest anthropometric predictor of left ventricular mass in the obese paediatric population - Shea, James R. (Cardiol Young, 2020)
BACKGROUND: Indexing left ventricular mass to body surface area or height(2.7) leads to inaccuracies in diagnosing left ventricular hypertrophy in obese children. Lean body mass predictive equations provide the opportunity to determine the utility of lean body mass in indexing left ventricular mass. Our objectives were to compare the diagnostic accuracy of predicted lean body mass, body surface area, and height in detecting abnormal left ventricle mass in obese children. METHODS: Obese non-hypertensive patients aged 4–21 years were recruited prospectively. Dual-energy X-ray absorptiometry was used to measure lean body mass. Height, weight, sex, race, and body mass index z-score were used to calculate predicted lean body mass. RESULTS: We enrolled 328 patients. Average age was 12.6 ± 3.8 years. Measured lean body mass had the strongest relationship with left ventricular mass (R(2) = 0.84, p < 0.01) compared to predicted lean body mass (R(2) = 0.82, p < 0.01), body surface area (R(2) = 0.80, p < 0.01), and height(2.7) (R(2) = 0.65, p < 0.01). Of the clinically derived variables, predicted lean body mass was the only measure to have an independent association with left ventricular mass (β = 0.90, p < 0.01). Predicted lean body mass was the most accurate scaling variable in detecting left ventricular hypertrophy (positive predictive value = 88%, negative predictive value = 99%). CONCLUSIONS: Lean body mass is the strongest predictor of left ventricular mass in obese children. Predicted lean body mass is the most accurate anthropometric scaling variable for left ventricular mass in left ventricular hypertrophy detection. Predicted lean body mass should be considered for clinical use as the body size correcting variable for left ventricular mass in obese children.